Theoretical and trustees' perspectives on the establishment of an Islamic social (Waqf) bank. Issue 1 (9th February 2015) - Haji Mohammad, Mohammad Tahir Sabit
Abstract : Purpose: – This paper aims to present an alternative to current banking systems. The purpose of the paper is the optimisation of the concept of cash waqf and its management in the framework of a waqf bank and its viability. Design/methodology/approach: – The study is doctrinal and empirical. Several assumptions concerning the structure and operation of the bank are made, surveyed and descriptively analysed. Findings: – The concept of cash waqf could be used for the operation of a waqf bank. There was a tendency among the given group of practitioners towards a corporate international social bank, capitalised by the waqf and non-waqf assets, sought after from the public and private sectors, as well as the Muslims and non-Muslims. Research limitations/implications: – Assumptions are basic. Empirical findings are based on the perspective of waqf trustees. Other stakeholders' perspectives need further research. Practical implications: – The study is expected to persuade for, and assist in the establishment of a waqf bank. Social implications: – This paper could contribute to the effectiveness of waqf institutions in their delivery of public good to the poor and society. These implications are not restricted to a specific country. Charities and the poor of any society may benefit from this study if the idea of total social banking is upheld. Originality/value: – This study is the first to address the structure and operation of a waqf bank empirically.